A comparative study on clean ammonia production using chemical looping based technology. (15th December 2020) - Lee Pereira, Reinaldo Juan; Argyris, Panagiotis Alexandros; Spallina, Vincenzo
Highlights: NH3 production using chemical looping can replace reforming technology. CO2 capture rate is >99% with a NH3 yield of 1.63 kgNH3 /kgNG . CO2 avoidance cost of negative 5 /ton has been achieved. The total plant cost of chemical looping is 19% lower than conventional process. Six large-scale packed bed reactors are needed for 500, 000 tonNH3 /y plant. Abstract: A comparative assessment of NH3 production using a chemical looping based process is carried out for 500, 000 tons per year with inherently integrated CO2 separation using natural gas as feedstock. The chemical looping process, with dynamically operated packed bed reactors, has been modelled, designed and simulated to accomplish steady-state operation and the results are used to carry out the full-scale energy analysis and costing. Two process heat management strategies have been considered on the basis of the oxygen carrier reactivity. With respect to the commercial process for natural gas-to-ammonia, the chemical looping based process replaces the syngas generation and purification units while the NH3 synthesis and purification units remain unvaried. The chemical looping plants show a yield of 1.54–1.63 kgNH3 /kgNG . The overall primary energy consumption to separate CO2 is 0.78–2.32 MJLHV /kgCO2 to achieve a carbon capture rate >99% compared to 73% achieved by the reference plant with integrated carbon capture and storage. The final cost of NH3 production is slightly lower than the reference technologies because of a decreased plant cost (19% lower) in particular for the reforming unit and CO2 separation. As a result, by using chemical looping the cost of CO2 avoidance is negative (−1 to −5 /tonCO2 ) and strongly dependent on the cost of the oxygen carriers and chemical looping reactors.